2016
DOI: 10.1002/btpr.2280
|View full text |Cite
|
Sign up to set email alerts
|

Using in situ nanocellulose‐coating technology based on dynamic bacterial cultures for upgrading conventional biomedical materials and reinforcing nanocellulose hydrogels

Abstract: Bacterial nanocellulose (BNC) is a microbial nanofibrillar hydrogel with many potential applications. Its use is largely restricted by insufficient strength when in a highly swollen state and by inefficient production using static cultivation. In this study, an in situ nanocellulose-coating technology created a fabric-frame reinforced nanocomposite of BNC hydrogel with superior strength but retained BNC native attributes. By using the proposed technology, production time could be reduced from 10 to 3 days to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Biomedical sector -Further current developments in the BNC field mainly concern novel carrier materials for cell cultivation [122,137,138], encapsulation of cells/immobilization of enzymes [139], coating of medical devices [140], and the production of BNC materials using the well-known oxygen-transparent silicone supports [141,142]. In case of medical implants a lot of results is reported not only in the field of soft tissue implants (see Section In vivo scaffolds) but also regarding materials for bone regeneration [121,143,144].…”
Section: Recent Developments In Bnc Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomedical sector -Further current developments in the BNC field mainly concern novel carrier materials for cell cultivation [122,137,138], encapsulation of cells/immobilization of enzymes [139], coating of medical devices [140], and the production of BNC materials using the well-known oxygen-transparent silicone supports [141,142]. In case of medical implants a lot of results is reported not only in the field of soft tissue implants (see Section In vivo scaffolds) but also regarding materials for bone regeneration [121,143,144].…”
Section: Recent Developments In Bnc Materialsmentioning
confidence: 99%
“…Using an in situ nanocellulose-coating technology based on dynamic bacterial cultures, Zhang et al [140] upgraded conventional biomedical materials, i.e., medical cotton gauze or other mesh materials. This fabric-reinforced BNC hydrogel was equivalent in gel characteristics of native BNC, and exhibited a qualitative improvement with regard to its mechanical properties.…”
Section: Recent Developments In Bnc Materialsmentioning
confidence: 99%
“…It has been reported that K. xylinus cells accumulate at the air/liquid interface (Tang et al , ), and the liquid phase that is far away from air might contain less oxygen, causing fewer cells to be distributed in the liquid phase. In the cellulose membrane, the living cells also have non‐uniform distribution in the vertical direction, where living cells mainly distribute in the shallow outer region of BNC membrane that is close to the air/oxygen, while in the deep inner region living cells can hardly be observed (Tang et al , ; Zhang et al , ). The limitation of this work is that the current living cell results are only relevant to the free cells suspended in the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…RDB can also be applied to the material coating. Zhang [58] used a roller-equipped horizontal bioreactor for in situ coating of cotton gauzes with BC, which also allowed cotton to act as an adequate material for K. xylinus culture, as porous matrices are more suitable for bacteria immobilization in RDB. Faster and higher productivity was observed when compared to static culture, with RDB-BC showing 2.61 mm sheets of BC and 1.62 g L À1 of BC in 3 days against 2.34 mm and 1.49 g L À1 of BC in 10 days in static culture.…”
Section: Rotating Disk Bioreactormentioning
confidence: 99%
“…[ [48][49][50][51][52][53]55] Vascular Grafts Water holding capacity, elasticity, biocompatibility or low inflammatory, makes BC a suitable material for artificial blood vessels. [57,58] Food applications Emulsion stabilizer BC NPs act as an oil-in-water emulsion stabilizer. [ [ 83,84] Energy production Bioethanol BC use as an alternative to lignocellulose from plants.…”
Section: Type Description Referencementioning
confidence: 99%